Utilizing Dalit Autobiographies in History - Jatin (Caste, 2023)
In the academic field, debates in the discipline of history largely contest whether the people whose narratives are absent in the dominant archives of knowledge, including Dalits, can be considered as devoid of history. Such contestations raise queries about the ways in which these groups form a sense of their past. In this light, can we consider cultural forms of narrative as reliable and ‘valid’ means to form an understanding of past, and to what extent? Can the cultural narrative forms, particularly autobiographical accounts, be utilized to reflect on the past of these communities? What methodologies does such an approach demand, and what challenges does it pose? This paper shall grapple with these intriguing inquiries. It attempts to position Dalit autobiographies and their utility in locating the sense of their past and in the larger knowledge production. This paper fundamentally proposes that Dalit autobiographies can lend crucial insights into the history of Dalit communities and beyond. These autobiographies can provide a perspective ‘from below’ and contribute to understanding how Dalits made sense of their past into narratives. I argue that Dalit articulation of their life experiences in the form of autobiographies not only rupture the assumptions of a singular past but also foregrounds the multiplicities and specificities to their everyday experiences.